2020
DOI: 10.3389/fbioe.2020.558375
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Stem Cell Therapy Bioengineering in Glioma

Abstract: Gliomas are a dismal disease associated with poor survival and high morbidity. Current standard treatments have reached a therapeutic plateau even after combining maximal safe resection, radiation, and chemotherapy. In this setting, stem cells (SCs) have risen as a promising therapeutic armamentarium, given their intrinsic tumor homing as well as their natural or bioengineered antitumor properties. The interplay between stem cells and other therapeutic approaches such as nanoparticles holds the potential to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 232 publications
0
20
0
Order By: Relevance
“…This is possible given that NP with diameters of at least 5–10 nm have reduced kidney excretion different from conventional chemotherapeutics. They are usually <1 kDa and filter more easily through the kidney [ 23 ]. Consequently, these particles have enough time to move from the bloodstream into the tumor tissue.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…This is possible given that NP with diameters of at least 5–10 nm have reduced kidney excretion different from conventional chemotherapeutics. They are usually <1 kDa and filter more easily through the kidney [ 23 ]. Consequently, these particles have enough time to move from the bloodstream into the tumor tissue.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Active targeting refers to the process that allows NP to selectively distribute into specific cell types or even intracellular compartments ( Figure 1 B) [ 23 ]. This involves the design of specific moieties for NP biofunctionalization.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, glioma has become one of the most commonly diagnosed types of cancer worldwide [1][2][3]. With the recurrence and metastasis ability of cancer cells, the number of patients diagnosed with malignant glioma is increasing [3][4][5]. Current anti-glioma therapies include chemotherapy and surgery, and previous research has shown that chemotherapy can improve the lifespan and quality of life of most glioma patients [6,7].…”
Section: Introductionmentioning
confidence: 99%